CLINICAL CHARACTERISTICS AND BODY COMPOSITION IN ELDERLY PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AT UNIVERSITY MEDICAL CENTER HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To determine clinical characteristics and body composition in elderly patients with chronic obstructive pulmonary disease at University Medical Center Ho Chi Minh City.Subject and methods: A cross-sectional study was conducted among 251 older patients (≥ 60 years old) with chronic obstructive pulmonary disease who visited the University Medical Center Ho Chi Minh City from December 2023 to May 2024. The information collected included socio-demographic characteristics, pathological characteristics, and anthropometric and body composition measurements.Results: The majority of the study subjects were male, accounting for 95.2%. With an average age of 71.8 ± 8.6 years. The majority of the pathologies were in the moderate and severe stages, accounting for 85.4%. More than 50% of the patients had concomitant chronic diseases. There were 29.5% subjects with malnutrition, as determined by BMI. The recorded body composition indices were: body fat percentage 25.0 ± 8.6 (%); fat-free mass 40.9 ± 6.4 (kg); skeletal muscle mass 21.9 ± 3.8 (kg); lean mass 38.7 ± 6.0 (kg); bone mineral mass 2.7 ± 0.4 (kg); basal metabolic energy/weight 23.2 ± 2.9 (kcal) and phase angle 4.5 ± 0.8 (o). There were statistically significant differences between men and women in the following characteristics: weight, height, body fat percentage, fat-free mass, skeletal muscle mass, lean mass, and bone mineral mass, with p
Keywords: Clinical characteristics, COPD, body composition